2018
DOI: 10.3847/1538-4357/aaae6c
|View full text |Cite
|
Sign up to set email alerts
|

Particle Acceleration Due to Cosmic-ray Viscosity and Fluid Shear in Astrophysical Jets

Abstract: An analytical model describing the acceleration of energetic charged particles due to cosmic-ray viscosity and fluid shear in radio jets based on the diffusive transport equation for cosmic rays is developed. The model indicates that laminar shear is not a significant mechanism for particle acceleration in nonrelativistic jets but may be important in relativistic jets. The model produces a power-law momentum spectrum of particles accelerated by the shear (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 81 publications
0
70
0
Order By: Relevance
“…A variety of topics and applications have been discussed in the context of gradual shear acceleration [e.g., 21,22,31,33,36]. In the following three recent results are briefly mentioned:…”
Section: Recent Applications Of Gradual Shear Accelerationmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of topics and applications have been discussed in the context of gradual shear acceleration [e.g., 21,22,31,33,36]. In the following three recent results are briefly mentioned:…”
Section: Recent Applications Of Gradual Shear Accelerationmentioning
confidence: 99%
“…All this suggests that a transversal velocity stratification is a generic feature of AGN-type jets. Given the challenges and complexity of observed emission properties, this has lead to a renewed interest in multi-zone/spine-shear layer acceleration and emission models [e.g., [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. One particularly interesting example concerns the emission properties of large-scale AGN jets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When taken together, this suggests that transversal velocity stratification and shear is a generic feature of AGN-type jets. Given the diversity of observed emission properties, this has in recent times generated new interest in multi-zone or spine-shear-layer acceleration and emission models (e.g., Sahayanathan 2009;Laing & Bridle 2014;Tavecchio & Ghisellini 2015;Rieger & Duffy 2016;Liang et al 2017;Chhotray et al 2017;Liu et al 2017;Kimura et al 2018;Webb et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When diffusive escape and radiative losses are neglected, non-relativistic gradual shear acceleration is known to lead to power-law particle spectra n(p) ∝ p 2 f (p) ∝ p −(1+α) for an energetic particle diffusion coefficient scaling as κ ∝ p α (Berezhko 1982;Rieger & Duffy 2006). With reference to an analytical steady state model based on the full particle transport equation, Webb et al (2018Webb et al ( , 2019 on the other hand recently showed that such hard power-law spectra are only achieved in relativistic shear flows, while the expected spectra become significantly softer for non-relativistic flow speeds. The present paper aims to explore and recapture this by means of a simple analysis.…”
Section: Introductionmentioning
confidence: 99%